2019
DOI: 10.1038/s41598-019-47098-4
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance All-Organic DFB and DBR Waveguide Laser with Various Grating Height Fabricated by a Two-Photon Absorption DLW Method

Abstract: Organic solid-state lasers (OSSLs) with distributed feedback (DFB) structures or distributed Bragg reflectors (DBRs) are promising for potential application in bio-sensing and hazardous materials detection. Here, the laser performances of the all-organic DFB waveguide lasers with various grating heights ranging from 0.4 to 4.7 μm were investigated. The grating structures used as the lasing cavity were fabricated using a two-photon absorption (TPA) direct laser writing (DLW) method with an SU-8 negative photore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Early OSSLs were realized by bulk optics 24 , but soon alternative designs have been developed. For example, vertical emission has been realized with vertical cavity surface-emitting lasers (VCSELs) 2527 , vertical external cavity surface-emitting organic laser (VECSOL) 28 , and Bragg gratings 17,22,2931 . However, the in-plane emission of the laser radiation into planar waveguides is a prerequisite for the application as an integrated light source in PIC devices.…”
Section: Introductionmentioning
confidence: 99%
“…Early OSSLs were realized by bulk optics 24 , but soon alternative designs have been developed. For example, vertical emission has been realized with vertical cavity surface-emitting lasers (VCSELs) 2527 , vertical external cavity surface-emitting organic laser (VECSOL) 28 , and Bragg gratings 17,22,2931 . However, the in-plane emission of the laser radiation into planar waveguides is a prerequisite for the application as an integrated light source in PIC devices.…”
Section: Introductionmentioning
confidence: 99%
“…21−29 The dependence of the grating height and pitch on the lasing threshold and the slope efficiency has been investigated for DFB and distributed Bragg reflector (DBR) waveguide laser devices based on rhodamine 6G (R6G) dyes dispersed in cellulose acetate (CA). 30,31 In a previous report, 32 we found that for DFB and DBR organic dye lasers, the preserved fluorescence emission and the enhanced slope efficiency for laser emission for R6G dye dispersed in a CA matrix were induced by the insertion of an intermediate layer consisting of a copolymer of vinylidene fluoride (VDF) and trifluoroethylene (TrFE) (P(VDF-TrFE)) between the waveguide layer and quartz substrate. The enhancement is considered to originate from the suppression of fluorescence concentration quenching by the introduction of polar crystals into the P(VDF-TrFE) intermediate layer.…”
Section: ■ Introductionmentioning
confidence: 98%
“…These approaches promise the suppression of aggregation-induced fluorescence quenching. Dendrimers and starburst polymers are a good option to prevent π–π stacking of phenyl rings in molecules. The dependence of the grating height and pitch on the lasing threshold and the slope efficiency has been investigated for DFB and distributed Bragg reflector (DBR) waveguide laser devices based on rhodamine 6G (R6G) dyes dispersed in cellulose acetate (CA). , …”
Section: Introductionmentioning
confidence: 99%
“…Much of this effort is and has been driven by the prospect of obtaining the long-sought after electrically pumped organic (or hybrid) laser, a device that it is finally becoming a reality [4,5]. In the process of reaching this final goal, many advances have been done in optically pumped devices, either developing new organic, inorganic or hybrid active materials [1][2][3][6][7][8][9][10][11], or optimizing the laser device fabrication and performance [1][2][3][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%